Prevalence and factors associated with utilisation of postnatal care in Sierra Leone: a 2019 national survey - Quraish Sserwanja; Lilian Nuwabaine; Kassim Kamara; Milton W. Musaba (BMC, 2022)
Abstract Background Within Sub-Saharan Africa, some countries still report unacceptably high rates of maternal and perinatal morbidity and mortality, despite improvements in the utilisation of maternity care services. Postnatal care (PNC) is one of the recommended packages in the continuum of maternity care aimed at reducing maternal and neonatal mortality. This study aimed to determine the prevalence and factors associated with PNC utilisation in Sierra Leone. Methods We used Sierra Leone Demographic and Health Survey (UDHS) 2019 data of 7326 women aged 15 to 49 years. We conducted multivariable logistic regression to determine the factors associated with PNC utilisation, using SPSS version 25. Results Out of 7326 women, 6625 (90.4, 95% CI: 89.9-91.2) had at least one PNC contact for their newborn, 6646 (90.7, 95% CI: 90.2-91.5) had a postnatal check after childbirth and 6274 (85.6, 95% CI: 85.0-86.6) had PNC for both their babies and themselves. Delivery by caesarean section (aOR 8.01, 95% CI: 3.37-19.07), having a visit by a health field worker (aOR 1.80, 95% CI: 1.46-2.20), having had eight or more ANC contacts (aOR 1.37, 95% CI: 1.08-1.73), having tertiary education (aOR 2.71, 95% CI: 1.32-5.56) and having no big problems seeking permission to access healthcare (aOR 1.51, 95% CI: 1.19-1.90) were associated with higher odds of PNC utilisation. On the other hand, being resident in the Northern (aOR 0.48, 95% CI: 0.29-0.78) and Northwestern regions (aOR 0.54, 95% CI: 0.36-0.80), belonging to a female headed household (aOR 0.69, 95% CI: 0.56-0.85) and being a working woman (aOR 0.66, 95% CI: 0.52-0.84) were associated with lower odds of utilizing PNC. Conclusion Factors associated with utilisation of PNC services operate at individual, household, community and health system/policy levels. Some of them can be ameliorated by targeted government interventions to improve utilisation of PNC services.